Enseigner l'évolution du vivant dans un contexte concordiste - SAÏDA AROUA; MARYLINE COQUIDÉ; SALEM ABBES (Metaichmio Publications, 2013)
Tunisia, Arab Muslim country, is characterized by a concordist socio-cultural context. Students mobilize conceptions of the diversity of life that are a mixture of religious and scientific knowledge. The teaching of the biological evolution described in this paper addresses these concepts in classroom debates that include epistemological reflections on the scientific characteristics of evolution as a historical science. During the teaching, students have developed different explanations, manifested a better understanding of what is scientific knowledge and finally, many of them developed separate explanations of the diversity of life.